Pharmacological Evaluation of Bioisosterically Replaced and Triazole-Tethered Derivatives for Anticancer Therapy - Kumar, Dipesh; Salahuddin; Mazumder, Avijit; Kumar, Rajnish; Ahsan, Mohamed Jawed; Yar, Mohammad Shahar; Abbussalam; Tyagi, Pankaj Kumar; Chaitanya, M.V.N.L. (Medicinal Chemistry, 2025)
Cancer has been the cause of the highest number of deaths in the human population despite the development and advancement in treatment therapies. The toxicity, drug resistance, and side effects of the current medicaments and therapies have left the void for more research and development. One of the possibilities to fill this void is by incorporating Triazole moieties within existing anticancer pharmacophores to develop new hybrid drugs with less toxicity and more potency. The placement of nitrogen in the triazole ring has endowed its characterization of being integrated with anticancer pharmacophores via bioisosteric replacement, click chemistry and organocatalyzed approaches. This review paper emphasizes the discussions from articles published from the early 2000s to the current 2020s about the triazole-based derivatives used in anticancer therapy, elaborating more on their chemical structures, target receptors or enzymes, mechanism of action, structure-activity relationships, different triazole-derived hybrid drugs under clinical and non-clinical trials, and recent advancements toward developing more potent and less toxic anticancer agents.
Keywords: triazole-tethered